Dielectric switching in correlation with the structural phase transitions in tetrapropylammonium perchlorate. Issue 2 (19th December 2022) - Trzebiatowska, Monika; Kowalska, Dorota A.; Gusowski, Marek A.; Jach, Ewelina; Ciżman, Agnieszka
Abstract : Crystals of the tetrapropylammonium perchlorate [(CH3 CH2 CH2 )4 N]ClO4, undergo two reversible structural phase transitions at 284 K and 445 K, they are accompanied by the structural and dynamic effects. Abstract : The crystals of the tetrapropylammonium perchlorate ([(CH3 CH2 CH2 )4 N]ClO4, TePrAClO4 ) compound undergo two reversible phase transitions: at ca. T 1 = 284 K and at ca. T 2 = 445 K. The observed phase transitions and distinct dielectric and relaxation effects are due to the dynamic motions of the organic cations and anionic framework. The crystals become ordered at low temperatures, then disordered at room temperature (propyl chains of the organic part as well as perchlorate ions are disordered over the mirror plane at c = 1/4 and 3/4) and highly disordered at high temperatures. The comparable changes in the wavenumber and FWHM shifts (IR and Raman spectroscopy) in the case of tetrapropylammonium and perchlorate ions in the phase transition at T 1 and slightly more significant changes for organic cations (juxtaposed with perchlorate ions) in the phase transition at T 2 lead to a conclusion that the phase transition at T 1 is equally driven by motions of the two ions, while the phase transition at T 2 is more influenced by the motions of organic cations. The phase transition at T 2 with its large entropy change resembles the behavior found in liquid crystals. The dielectric function values can be switched and tuned in the low- and high-dielectric states, which may indicate the potential application of this material in sensors or actuators.